தக்கன் வேள்வி / Thakkan Velvi - சி. கல்பனா/S. Kalpana; முனைவர் மு. நவமணி/Dr. M. Navamani (Chenkaantal)
It is religion that matures and guides human society. Religious concepts are not easily grasped by people who are steeped in ignorance. Therefore, illustration through simple stories is the norm. Thus the Velvi of Thakkan is the best evidence in the world of Saivism. It is to highlight that high devotion and love is destroyed by arrogance and to realize that God is merciful in any situation. Pharani Ottakoothar brings this story to the rise of Saivism and creates religious awareness. The human mind is capable of wanting to get what it wants. Along with that, he thinks that he is great. Self-esteemed and immersed in ignorance, it is unable to cut off the birth and continues to suffer. Therefore, Saivism prioritizes elimination of egoism. Those who live arrogantly will be humbled even from high places. The blessed ones explain this through the Purana. Thakkan's Velvi is a symbol of Saivism. It is written by Ottakkootha, who prefaces the velvi of Dakkana. This book highlights the influence of Saivism in those days. This article will examine the Thakkan Vellavi.